Empowering Islamic Values: The Role of Madrasah Head Leadership in Extracurricular Enrichment - Subaidi, Subaidi; Arsyad, Junaidi; Kisworo, Angen Yudho (JURNAL AL-TANZIM, 2024)
This research aims to analyze the leadership of madrasa heads in developing Islamic culture through extracurricular activities. A qualitative approach with case study methods is used to gain an in-depth understanding of leadership practices and their implementation. Data was collected through in-depth interviews, participant observation, and document analysis. The research results show that the madrasa head's adaptive and inspiring leadership plays a vital role in strengthening Islamic values among students. The madrasa head is the main driver in aligning the vision with daily activities, including extracurricular activities designed to develop student's character and spirituality. The implications of this research highlight the importance of visionary and strategic leadership in creating an educational environment conducive to forming Islamic character and morals. The implication of this research is the importance of visionary and participatory leadership of madrasah heads in developing Islamic culture through extracurricular activities to strengthen students' moral and spiritual values. The Mediating Role of Devolved Management on the Influence of Organizational Support on Teacher Creativity